Media, Margins and Civic Agency
XIII, 219 p.
Keywords: This collection brings together new research on contemporary media, politics and power. It explores ways and means through which media can and do empower or dis-empower citizens at the margins that is, how they act as vehicles of, or obstacles to, civic agency and social change.